Online Consumer Preference For Local Culinary: Systematic Literature Review Variable - Aulia Rahmi, Vembri; Sudarmiatin, Sudarmiatin (Publisher Cv. Inara, 2022)
The study aims to explore the trends of several studies of consumer preferences for local culinary products that have been around for a decade. The consumer behavior theory approach is more widely used in the analysis of consumer preferences for local culinary research. The research method in this study uses a literature review approach, precisely systematic review with the collection of reputable journal-based data obtained from searches on google scholar databases as well as qualitative methodologies for evaluating and synthesizing findings from several studies in the past. The results showed that some studies on consumer preferences for local cuisine were influenced by some predictors of consumer attitudes towards local cuisine. Literature review on local culinary-based research relates to culinary tourism destinations, including the field of hospitality. Consumer segmentation is influenced by how purchasing behavior is for local culinary.